Controlling Pre-operative Anxiety with Self Relaxound Therapy - Sulastri, Sulastri; Nurhidayah, Sri Melati (Poltekkes Kemenkes Tanjung Karang, 2024)
The impact of anxiety before surgery can affect the operation, so it must be postponed. Action is needed to overcome the anxiety experienced by the patient. One that can be done by giving self relaxound therapy is by providing a combination of relaxation interventions, maybe, and natural sounds developed by researchers, which is done by perception and self-suggestion while listening to natural sounds and deep breathing exercises. This research aims to determine the effect of relaxation self relaxound on patient anxiety before laparotomy surgery. This type of research uses quantitative research by designing a quasi-experiment using a nonplan equivalent without a control group. This research was carried out in the surgical inpatient room on 32 respondents. Anxiety measurement uses a questionnaire called the Zung Self Rating Scale. Data analysis was done using a paired sample T-test with a significance limit 0.05. The analysis results obtained a p-value=0.000 (α<0.05), which shows a significant effect between therapy self relaxound and patient anxiety. Psychological problems are closely related to surgery; for this, the researchers suggest self relaxound therapy can be considered as a nursing procedure for every pre-operative patient.